Contribution des applications non expansives en la théorie du point fixe et applications - Heddi, Kaddouri; Tamma, Khouloud (My University, 2017)
Dans ce travail, après la définition de certains concepts de base de l’analyse fonctionnelle, nous avons étudié le théorème du point fixe se rapportant à chacune des applications α-non expansives et à chacune des applications non expansives généralisées. En plus nous avons abordé l’étude du théorème de Krasnoselskii du type non expansive et enfin, comme application, nous avons étudié l’existence et de l’unicité de la solution pour les équations différentielles à retardIn this work, after defining some basic concepts of functional analysis, we have studied the fixed point relating to each of the non-expansive applications and to each of the generalized non-expansive applications. In addition, we studied α-non expansive type of Krasnoselskii's theorem and finally, as an application we have studied the existence and the uniqueness of the solution for the delay differential equations
memoier master mathematique
Keywords: fixed point, non expansive mappings, differential equations with delay; point fixe, applications non expansives, équations différentielles à retard.